A Systematic Review of the Effects of Adding Neostigmine to Local Anesthetics for Neuraxial Administration in Obstetric Anesthesia and Analgesia. Issue 2 (June 2016) - Cossu, A.P.; De Giudici, L.M.; Piras, D.; Mura, P.; Scanu, M.; Cossu, M.; Saba, M.; Finco, G.; Brazzi, L.
Abstract : ( Int J Obstet Anesth. 2015;24:237–246) Neostigmine, an acetyl-cholinesterase inhibitor, has been used for both epidural and intrathecal anesthesia in obstetric patients. In order to quantify its benefits and/or adverse effects as an adjuvant in neuraxial anesthesia, the authors of this meta-analysis reviewed randomized, placebo-controlled studies in which neostigmine was administered in combination with local anesthetics or other adjuvants.